Leadership Ethics in the Islamic Education System: A Theoretical and Practical Study in Educational Institutions - Tri Handayani; Novyanti, Elva; Asha, Lukman; Warlizasusi, Jumira; Fakhrudin, Fakhrudin (Yayasan Corolla Education Centre, 2025)
This article aims to explore and analyze the concept and implementation of ethical leadership within the Islamic education system from both theoretical and practical perspectives. The data in this study were analyzed using a qualitative descriptive method through library research. The researchers collected information from academic journals, books, and policy documents related to Islamic education and leadership ethics. They then used content analysis to review and compare the information, looking for patterns and key ideas. The analysis was guided by theories of ethical leadership and focused on how these ideas are applied in real Islamic educational institutions. The findings indicate that ethical leadership plays a central role in strengthening organizational culture, managing conflict, enhancing work motivation, and improving strategic decision-making in Islamic educational institutions. Core values such as honesty, trustworthiness, justice, deliberation, and exemplary behavior are essential foundations that must be internalized by every Islamic educational leader. The prophetic leadership model, which emphasizes moral and spiritual dimensions, is considered ideal for developing transformative and competitive educational institutions. Therefore, strengthening ethical leadership is a strategic necessity for realizing a quality and character-based Islamic education system.